Clinical analysis of the trigger thumb of childhood - Herdem, Mustafa; Bayram, Hüseyin; Toğrul, Emre; Sarpel, Yaman (The Turkish Journal of Pediatrics, 2003)
Trigger thumb of childhood, termed congenital trigger thumb, is a pathology of the flexor pollicis longus tendon with an unknown etiology. In this study, treatment outcomes of 47 trigger thumbs of 36 children were evaluated. There were 18 males and 18 females with a mean age of 34 months (9 months-13 years). Average age of recognition of pathology by the family was 20.5 months (0-8 years). In seven of 11 bilateral cases pathology was recognized simultaneously while in the other four, diagnosis was made at different times. We used conservative treatment for all patients under three years of age, which was unsuccessful. Thus, surgical relase was performed in all cases. In the mean follow-up of seven years (range 5-15), contracture and palpable nodules disappeared. In conclusion, we believe trigger thumb in childhood should be treated surgically and that the term "congenital trigger thumb" should be changed to "developmental trigger thumb".